The transposition of a Philosophy subject matter. C.S. Peirce as ‘knowledge to be taught’ - Agrati, Laura Sara (The education review, USA, 2019)
The school mediation acts as 'integration' (Chocran, 1997) of a subject matter: it transforms cultural objects and produces new knowledge. Referring to the theoretical model of PCK (Pedagogical Content Knowledge - Shulman, 1986, 1987), of 'Didactic transposition' (Chevallard, 1991; Develay, 1992, 2015; Waquet, 2015) and to a previous study addressing the process of integration of a Philosophy subject matter (G.B. Vico, Agrati, 2019), this study was conducted on the I phase of transposition that is made by the editors and authors of textbook through the contents selected (Kang & Kilpatric, 1992; Clement, 2007; Vaz, 2017). The paper presents further results of a second exploratory study aimed at detect the main topics of C.S. Peirce, found in textbooks and how these have been made explicit by the texts/graphic organizers. The textbook analysis (O' Keeffe, 2013; Chiappetta et al., 1993) was carried out through a comparison of textual-graphic devices used by two philosophy textbooks: it was conducted on the index of the entire textbook and on the sections related to the American philosopher and it used 'ad hoc' analysis criteria - content (selection of topics and prevailing links), structure (sequence and articulation of topics within the whole work) and language (meaning of terms and technical vocabulary) (Valverde at al., 2002; Rivers, 1990). The findings are about the contents' modification - more extended or more reduced compared to the main topics (v. belief, abduction, semiotics) - and the topics' explication (v. neologisms and metaphors); they confirm and make explicit the work of transformation made by the textbooks' authors which elaborate a 'knowledge to teach' (Develay, 2015) different than the 'scholarly knowledge' and that could condition the teaching process and the student's learnings.